Costs and health consequences of chlamydia management strategies among pregnant women in sub-Saharan Africa. Issue 7 (11th October 2007) - Romoren, M; Hussein, F; Steen, T W; Velauthapillai, M; Sundby, J; Hjortdahl, P; Kristiansen, I S
Abstract : Objectives: Chlamydia is the most common bacterial sexually transmitted infection worldwide and a major cause of morbidity—particularly among women and neonates. We compared costs and health consequences of using point-of-care (POC) tests with current syndromic management among antenatal care attendees in sub-Saharan Africa. We also compared erythromycin with azithromycin treatment and universal with age-based chlamydia management. Methods: A decision analytical model was developed to compare diagnostic and treatment strategies, using Botswana as a case. Model input was based upon (1) a study of pregnant women in Botswana, (2) literature reviews and (3) expert opinion. We expressed the study outcome in terms of costs (US), cases cured, magnitude of overtreatment and successful partner treatment. Results: Azithromycin was less costly and more effective than erythromycin. Compared with syndromic management, testing all attendees on their first visit with a 75% sensitive POC test increased the number of cases cured from 1500 to 3500 in a population of 100 000 women, at a cost of US38 per additional case cured. This cost was lower in high-prevalence populations or if testing was restricted to teenagers. The specific POC tests provided the advantage of substantial reductions in overtreatment with antibiotics and improved partner management. Conclusions: Using POC tests to diagnose chlamydia during antenatal care in sub-Saharan Africa entails greater health benefits than syndromic management does—and at acceptable costs—especially when restricted to younger women. Changes in diagnostic strategy and treatment regimens may improve people's health and even reduce healthcare budgets.